Impact of Reputation of Public Accounting Firms as Mediating Between Leverage, Profitability and Company Size Against Audit Delay of Large Trading Companies on Indonesia Stock Exchange - Astuti Astuti; Supitriyani Supitriyani; Lenny Dermawan Sembiring (Jurnal Maksipreneur, 2022)
Financial statements delivered promptly are useful in analyzing and making decisions in the economic field that can contribute to national economic growth. The timeliness of financial statements on the results of the audit report can also affect the value of the financial statements. This research aims to determine the influence of leverage, profitability, and company size on audit delay as well as the impact of the reputation of public accounting firms (KAP) as a mediating influence of leverage, profitability, and company size towards audit delay. This research was conducted on twenty Large Trading Companies during the period 2015-2019 which totaled 100 data. The data analysis techniques used in this research are descriptive statistical analysis, classical assumption test, multiple regression analysis, and hypothesis testing. The results showed that partially leverage, profitability, and KAP’s reputation had an insignificant influence on audit delay, while the company size has a significant influence on audit delay. Furthermore, the reputation of public accounting firms can moderate the influence of leverage on audit delay but is unable to moderate the influence of the company size and profitability on audit delay.